Population Forecast of Nepal from Population Growth Trend (2001-2021) - Raut, Rekha; Katuwal, Khadga Bahadur; Basnet, Kirti Bhushan (Educational Journal, 2026)
Number of projected populations are crucial to effective infrastructure and social services, as well as economic planning needed in Nepal. This study investigates the demographic transition of Nepal by exploring the census data on 2001, 2011 and 2021 which was a time characterized great socioeconomic transformation. The aim of this study is to analyze changing growth patterns and deliver a robust population prediction with arithmetic, geometric, and exponential growth models. Inter-census growth rates and information on population doubling times by broad ecological, development and socio-political regions were calculated. The report showed a steep trend decline from 2.25% in the period between 2001 and 2004, to.92% from 2018 to 2021. Therefore, the population doubling time has increased considerably; according to the exponential model, the doubling interval extended from 49.65 years (with reference to the trends from 2001-2011) to 72.23 years (with reference to the trends from 2011-2021). If the same growth rate of 1.1% continues, Nepal’s population is projected to stand at approximately 32.55 million by 2031 and increase to about 36.31 million by 2041. These results indicate a transition from "population explosion" to stabilized demographic profile led by increased migration, rapid urbanization 28.22% in 2021 and decreased fertility. This paper provides empirical evidence of demographic transition for a developing economy across Himalayan regions, which will help demographers to identify the slowing momentum of growth towards population control and work towards sustainable urban resource handling linking with regional development through policymakers.